Discriminação salarial por raça e gênero no mercado de tabalho das regiões Nordeste e Sudeste do Brasil: uma aplicação de simulações contrafactuais e regressão quantílica - Cambota, Jacqueline Nogueira (2005)
This paper analyses the discrimination of wages by race and gender in the wage distributions according to sectors of occupation, comparing the Northeast and Southeast regions of the Brazil. For this aim, we use data from Pnad 2002 and apply a semi-parametric method - kernel estimator and another parametric – quantile regression. In the first, we make counterfactual exercises, to examine how going to be the wage distribution of the black(women) workers if they had the same schooling than the white (men) workers. The results verify that exist discrimination against women and black workers in labor market of both regions. The kernel method provided a visually clear representation that discrimination against black workers is greater in the Southeast for all sectors, while it can not identify where discrimination against women is greater because it depend on the sector. The quantile regression showed that discrimination increases for higher wages.